Engineering the AAVS1 locus for consistent and scalable transgene expression in human iPSCs and their differentiated derivatives - Oceguera-Yanez, Fabian; Kim, Shin-Il; Matsumoto, Tomoko; Tan, Ghee Wan; Xiang, Long; Hatani, Takeshi; Kondo, Takayuki; Ikeya, Makoto; Yoshida, Yoshinori; Inoue, Haruhisa; Woltjen, Knut (Methods (San Diego, Calif.), 2016)
•Reliable targeting to the AAVS1 requires robust positive selection.•Reporter expression from the CAG promoter is reproducible, scalable, and stable.•Reporter expression is retained following differentiation to multiple lineages.•Fluorescent and luminescent iPSCs have value in disease modeling and transplantation studies. The potential use of induced pluripotent stem cells (iPSCs) in personalized regenerative medicine applications may be augmented by transgenics, including the expression of constitutive cell labels, differentiation reporters, or modulators of disease phenotypes. Thus, there is precedence for reproducible transgene expression amongst iPSC sub-clones with isogenic or diverse genetic backgrounds. Using virus or transposon vectors, transgene integration sites and copy numbers are difficult to control, and nearly impossible to reproduce across multiple cell lines. Moreover, randomly integrated transgenes are often subject to pleiotropic position effects as a consequence of epigenetic changes inherent in differentiation, undermining applications in iPSCs. To address this, we have adapted popular TALEN and CRISPR/Cas9 nuclease technologies in order to introduce transgenes into pre-defined loci and overcome random position effects. AAVS1 is an exemplary locus within the PPP1R12C gene that permits robust expression of CAG promoter-driven transgenes. Gene targeting controls transgene copy number such that reporter expression patterns are reproducible and scalable by ∼2-fold. Furthermore, gene expression is maintained during long-term human iPSC culture and in vitro differentiation along multiple lineages. Here, we outline our AAVS1 targeting protocol using standardized donor vectors and construction methods, as well as provide practical considerations for iPSC culture, drug selection, and genotyping.